Transport properties of Lu₂Fe₁₇ single crystals under extreme conditions - Skorokhod, Y.; Arnold, Z.; Kamarad, J.; Andreev, A.V. (Functional Materials, 2004)
Presented are the measurement results of Lu₂Fe₁₇ single crystals electrical resistivity under hydrostatic pressure up to 1.1 GPa and magnetoresistance in magnetic fields up to 12 T in temperature range 5-300 K. A large increase of resistivity has been observed due to transition from ferromagnetic phase to pressure-induced helical antiferromagnetic one. The simultaneously measured resistivities along the a and c crystallographic directions confirm the strong anisotropic behavior of Lu₂Fe₁₇ resistivity, a remarkably lower resistivity being observed along the a axis. The magnetoresistance values measured along c and a axes under identical conditions also are different. The magnetoresistance ratio for the a direction was found to be smaller than for the c one.